La Gestión del Talento Humano y productividad en la unidad de servicio al asegurado del hospital general Riobamba IESS - Tixi Chacha, Johana Alexandra (2025)
This study aimed to determine how Human Talent Management influences productivity in the Policyholder Service Unit of the General Hospital of Riobamba IESS. The research was established using a descriptive method and a non-experimental design with a hypothetical deductive approach. The head of the Human Resources Administrative Unit was interviewed, and a survey consisting of 13 questions was administered to 22 employees in the USA. On the other hand, the SPSS program was used to analyze the data, verifying the normality and reliability of the instruments using the Shapiro-Wilk test and Cronbach's Alpha. The results indicated that human talent management does influence the unit's productivity. The personnel selection and evaluation processes are structured, but there are deficiencies in training and personnel assignment. The lack of diversity in training, the absence of incentives, and insufficient adaptation to technological tools were identified as areas for improvement. In addition, although the use of technology is positive, its implementation lacks adequate personnel training. To conclude, human talent management affects the institution's performance. Thus, implementing the competency- based model establishes a clear connection with efficiency in the USA of the Riobamba General Hospital IESS, incorporating recruitment, training, and performance evaluation processes based on skills. This model is intended to maximize the performance of employees, ensure the achievement of work objectives, and raise the quality of service offered to the insured.